Analisis Emisi Gas Buang dengan Memvariasikan Tekanan Nozzel Kenderaan Roda Empat 2300cc : Penelitian - Positron Bangun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze exhaust gas emissions by varying nozzle pressure and engine speed using a 2300 cc engine stand with diesel fuel. Exhaust emissions were measured with an engine smoke tester at engine speeds of 1000 rpm, 2000 rpm, and 3000 rpm, combined with nozzle pressures of 130 kg/cm², 140 kg/cm², and 150 kg/cm². The collected data were tabulated and analyzed using Microsoft Excel. The results show that variations in nozzle pressure and engine speed affect exhaust emissions. The lowest HC emission value (ppm) occurred at a nozzle pressure of 130 kg/cm² and 1000 rpm, while the lowest CO emission value (%) was recorded at a nozzle pressure of 140 kg/cm² and 3000 rpm.